Reframing the politics of natural resource governance in Africa: Insights from the local content legislation process in Ghana. Issue 1 (24th January 2022) - Ayanoore, Ishmael; Hickey, Sam
Abstract: New oil‐producing countries in Sub‐Saharan Africa have moved rapidly to adopt local content legislation to ensure that locally owned firms benefit from natural resource finds. Current research into this move frames local content development in Africa as existing on a continuum between elite projects to accumulate rents and build a domestic capitalist class. This article problematizes such accounts through an in‐depth case study of Ghana. By deploying an adapted "political settlements" framework that incorporates the role of ideas as well as transnational agency, we show that elite commitment to local content reforms is driven by the broader politics of regime survival and paradigmatic ideas rather than political economy factors alone. Related Articles: Anuar, Amalina, and Aninda Dewayanti. 2021. "Trust in the Process: Renewable Energy Governance in Malaysia and Indonesia." Politics & Policy 49(3): 740–70. https://doi.org/10.1111/polp.12409 Khodr, Hiba, and Isabella Ruble. 2013. "Energy Policies and Domestic Politics in the MENA Region in the Aftermath of the Arab Upheavals: The Cases of Lebanon, Libya, and KSA." Politics & Policy 41(5): 656–89. https://doi.org/10.1111/polp.12033 Osman, Antwi‐Boateng, and Mamudu Abunga Akudugu. 2020. "Golden Migrants: The Rise and Impact of Illegal Chinese Small‐Scale Mining in Ghana." Politics & Policy 48(1): 135–67. https://doi.org/10.1111/polp.12342 Abstract : Reformular la política de la gobernanza de los recursos naturales en África: perspectivas del proceso de legislación de contenido local en Ghana: Los nuevos países productores de petróleo del África subsahariana se han movido rápidamente para adoptar una legislación de contenido local para garantizar que las empresas de propiedad local se beneficien de los hallazgos de recursos naturales. La investigación actual sobre este movimiento enmarca el desarrollo de contenido local en África como existente en un continuo entre proyectos de élite para acumular rentas y construir una clase capitalista nacional. Este artículo problematiza tales relatos a través de un estudio de caso en profundidad de Ghana. Al implementar un marco adaptado de "acuerdos políticos" que incorpora el papel de las ideas y la agencia transnacional, mostramos que el compromiso de la élite con las reformas de contenido local está impulsado por la política más amplia de supervivencia del régimen y las ideas paradigmáticas en lugar de factores de economía política únicamente. Abstract : 重新建构非洲自然资源治理政治：加纳国产化立法过程得出的见解: 撒哈拉以南非洲的新石油生产国已快速采取国产化立法，确保本地公司从自然资源发现物中获益。关于该立法的现有研究认为，非洲的本地资源开发依赖于一系列精英计划之间的连续体，目的是积累租金和建立一个国内资本主义阶级。本文以加纳作为深度案例研究，对这类研究发现进行问题化。通过住用一项调整过的"政治解决"框架（包括观念的作用和跨国家行动力），我们表明，精英对国产化改革的承诺受关于政权生存和范式观点的更广政治所驱动，而不仅仅是政治经济因素。